Effect of Ethanol and Petroleum Ether Extracts of Some Medicinal Plants on Sclerotiumrolfsii, Causal Agent of Postharvest Rot of Yam (Dioscorea Spp.) - F. U, Nweke (Review of Plant Studies, 2015)
Ethanol and Petroleum ether of leaves of Azadirachtaindica A. Juss, Citrus aurantifolia (Christm.)Swingle, Jatrophacurcas L., Anacardiumoccidentale L., seeds of Garcinia kola Heckel and peels of Citrus sinensisOsbek were studied for in vitro activity against mycelial growth and sclerotium germination of Sclerotiumrolfsii, Sacc., the causal agent of postharvest yam rot. The phytochemical screening of the extracts of the medicinal plants revealed the presence of alkaloids, flavonoids, glycosides, steroids, saponins, tannins and terpenoids. The ethanol and petroleum ether extracts showed varying levels of fungitoxicity activity with the ethanol extracts being more effective. Mycelial growth of S. rolfsii was significantly (P < 0.05) reduced by ethanol extracts of C. sinesis (89.63 – 100%), C. aurantifolia (67.04 – 83.28%) and A. indica (53.70 – 69.38%) during the period of incubation. Sclerotium germination was also significantly (P < 0.05) reduced by ethanol extracts of C. sinesis (87.50%), C. aurantifolia (62.50%) and A. indica (50%). This study showed the potentials of extracts of some plant products to control S. rolfsii in yam.